Santri Disciplinary Punishment Under the Child Protection Law Perspective: Hukuman Disiplin Santri Dalam Perspektif Undang Undang Perlindungan Anak - Purnanda, Ledian; Adisel, Adisel; Riadi, Dayun (Indonesian Journal of Innovation Studies, 2026)
General Background: Islamic boarding schools play a significant role in shaping students’ moral character and discipline through structured educational practices. Specific Background: Within pesantren education systems, disciplinary punishment is commonly applied to maintain order and encourage responsibility among santri. Knowledge Gap: However, growing public concern regarding children’s rights raises questions about whether disciplinary practices in pesantren align with the legal principles of child protection. Aims: This study aims to analyze the forms of punishment implemented at Pondok Pesantren Modern Darussalam Kepahiang and examine their compatibility with the provisions of the Child Protection Law. Results: Using a qualitative descriptive approach with data collected through observation, interviews, and documentation, the study identifies three main categories of punishment: physical, psychological, and social sanctions. These disciplinary measures are generally intended to foster discipline, responsibility, and moral awareness rather than to cause harm. When implemented within educational boundaries, the practices are considered consistent with Articles 54 and 59 of the Child Protection Law, while teachers are also legally protected under Law No. 14/2005 on Teachers and Lecturers. Novelty: This research provides a pedagogical and juridical analysis of pesantren disciplinary practices by integrating perspectives of Islamic educational tradition with national child protection regulations. Implications: The findings highlight the importance of establishing clear disciplinary guidelines and providing training for educators to ensure that punishment practices remain educational, ethical, and legally compliant in pesantren environments. Highlights • Identification of three disciplinary sanction categories applied in Islamic boarding school environments• Psychological responses of students reveal varied perceptions toward institutional discipline practices• Absence of formal disciplinary guidelines indicates the need for structured regulatory frameworks Keywords Islamic Boarding School; Child Protection Law; Santri Discipline; Educational Punishment; Pesantren Education